The Degree of Effectiveness of The Management of Women in Administrative Empowerment and Its Obstacles at The Branches of Hail University from The Point of View of Faculty Members - BaniHani, Maysaa hasan muflih (Journal of Educational and Psychological Sciences, 2020)
The purpose of this study was to investigate effectiveness of female administration in the Administrative Empowerment at Hail University branches and its impediments, from the point of view of the faculty members. The researcher used the descriptive analytical approach. The questionnaire was the tool of study and the study sample consisted of (53) of female faculty members at Hail University branches during the first semester 2018- 2019. The results of this study found that the overall degree of administrative empowerment was obtained at a general average (3.93) i.e. high degree and at the dimensional level. Indeed, the work team term was in the first rank with an average of 4.09, and then it comes the delegation of authority with an average of (3.89). The communication term comes at the third level with an average of (3.88) and in the last rank, it comes the motivation of the staff with an average of (3.86) and all of them with a rating of (high). As regard the obstacles in the women administration, the administrative impediments obtained the first rank with an average of (3.87) followed by the personal constraints with an average of (3.76), and then the political impediments with an average of (3.47), and finally the social obstacles with an average of (2.61). For instance, the study showed that there were no significant differences due to the impact of experience years and the impact of scientific qualification. There were some recommendations according to the study results, which were to increase the effectiveness of faculty members and remove obstacles facing them.